2020
DOI: 10.1002/adma.202005448
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Piezoelectric and Magnetostrictive Biosensor Materials for Detection of COVID‐19 and Other Viruses

Abstract: fever with or without chills, chest tightness, dry cough, and shortness of breath, while developing patchy to diffuse infiltration of the lungs, as shown radiographically in Figure 1. Identifying and monitoring SARS-CoV-2 infection has become crucially important. A recent projection of the transmission dynamics of SARS-CoV-2 [2] showed that longitudinal serological studies are desperately needed to determine the extent and duration of immunity to SARS-CoV-2. Even in the event of apparent elimination, maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 195 publications
(134 citation statements)
references
References 134 publications
(215 reference statements)
0
132
0
2
Order By: Relevance
“…The virus can be inactivated by altering the stability of this protein. Various physical ( e.g ., temperature and adsorption) and chemical ( e.g ., pH, disinfectants and surface modification) methods have been explored to test the stability of the spike protein ( Narita et al, 2021 ; Pandey, 2020a ; Pandey, 2020b ). It has been reported that SARS-CoV-2 remains stable on different surfaces but can be inactivated by heating at a temperature greater than 65 °C for more than 5 minutes of duration ( Abraham et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The virus can be inactivated by altering the stability of this protein. Various physical ( e.g ., temperature and adsorption) and chemical ( e.g ., pH, disinfectants and surface modification) methods have been explored to test the stability of the spike protein ( Narita et al, 2021 ; Pandey, 2020a ; Pandey, 2020b ). It has been reported that SARS-CoV-2 remains stable on different surfaces but can be inactivated by heating at a temperature greater than 65 °C for more than 5 minutes of duration ( Abraham et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it could play the role as an energy harvesting fiber to power other two PZT fibers for virus detection. This is a challenging research area [ 27 ], and later some progress will be made.…”
Section: Resultsmentioning
confidence: 99%
“…197 Molecular noses, and dogs have also been proposed as a means to identify CoVID-19 sufferers, although these seem a long way off deployment. 198 Several nanotechnology-based strategies have also been reported, 199 although again these seem a long way from even entering trials. Chest computed tomography (CCT) procedures were shown to be 97% accurate, 56% specific and 72% accurate by a group from Italy, 200 which agrees with previous data from a group from China.…”
Section: Other Diagnostic Methodsmentioning
confidence: 99%